DISPLAY POSITION DETERMINATION PROGRAM, RECORDING MEDIUM WITH THE PROGRAM RECORDED THEREON, AND DISPLAY POSITION DETERMINATION APPARATUS AND METHOD - YAMAMOTO YOSHIAKI; YOSHIMURA RYUSUKE; MIYAWAKI MASARU; MIURA KASUMI (2009)
PROBLEM TO BE SOLVED: To reduce workloads and shorten working hours by displaying balloon graphics in an appropriate display position, even under the conditions where a small space area remains in a display screen. SOLUTION: A program includes: selecting a component Ob3 from among component groups to be displayed; acquiring a display share for the display screen D every component Ob1 to Ob3; determining whether a balloon graphic B3 can be displayed with respect to the selected component Ob3 in the non-display area where the component groups in the display screen D are not displayed; retrieving the component Ob1 in which the acquired display share exceeds a predetermined threshold, when determined undisplayable in the non-display area; and deciding the display area of the balloon graphic B3 with respect to the component Ob3 in the display area of the retrieved component Ob1. COPYRIGHT: (C)2010,JPO&INPIT